The Penguin book of business wisdom a must-have collection and anecdotes for every business situation - Dando-Collins, Stephen (Penguin Books 2000)
Hitting the target is crucial in business so every bit of wisdom helps.With this in mind Stephen Dando-collins has packed the penguin book of Business Wisdom with thoughts,advice anecdotes and hard-learned lessons on issues and themes related to business.
Keywords: Business-Quotations, maxims, etc